1990
DOI: 10.1017/s0014479700018184
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Source-Sink Relations in Cassava Using Reciprocal Grafting

Abstract: S U M M A R YSource-sink relations in cassava were investigated following reciprocal grafting among three cultivars of different yield groups. Both rootstock and scion had significant effects on net assimilation rate and tuber yield, demonstrating that both sink capacity and source activity are important in achieving maximum tuber yield. The scion had no effect on tuber dry matter percentage and starch content of the grafts but the hydrocyanic acid content of the tuber was significantly influenced by both root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In line with other grafting experiments in cassava (Dahniya et al, 1982;Ramanujam and Ghosh, 1990), we also found that both source and sink capacities were important for determining storage root yield. However, Dahniya et al (1982) and Ramanujan and Ghosh (1990) did not link sink capacity and sink limitation to storage root number.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with other grafting experiments in cassava (Dahniya et al, 1982;Ramanujam and Ghosh, 1990), we also found that both source and sink capacities were important for determining storage root yield. However, Dahniya et al (1982) and Ramanujan and Ghosh (1990) did not link sink capacity and sink limitation to storage root number.…”
Section: Discussionsupporting
confidence: 91%
“…In beet, the genetic determination of storage organs appears to be a dominant factor in root-shoot relations (Rapoport and Loomis, 1985). In cassava, Ramanujam and Ghosh (1990) and Dahniya et al (1982) used grafted material to demonstrate that both scion and stock are important for achieving high yield. However, they did not indicate how root sink capacity could be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, several researchers have used grafting methods to increase root production of cassava. In these studies, genotypes with high photosynthetic potential were used as scions and genotypes with high fresh root yield as rootstock ( Ahit et al, 1981 ; Dahniya et al, 1982 ; Ramanujam and Ghosh, 1990 ). The results showed that grafting in adult plants did not influence the production of roots, starch and dry matter content, similar to the results found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the graft on the rootstock with respect to leaf area, gas exchange, aerial biomass, and net assimilation rate has been studied in cassava (Ramanujam and Ghosh, 1990;Pellet and El-Sharkawy, 1994), but there has been no study of the effects on anatomic structure. Anatomic studies of grafted cassava serve to evaluate grafting potential in cassava breeding.…”
Section: Introductionmentioning
confidence: 99%